Streptokinase-Based Pharmacoinvasive Strategy Versus Primary Percutaneous Coronary Intervention: A Propensity Score Matching Analysis from the Siriraj STEMI Network - Towashiraporn K. (2023)
Objective: To investigate the efficacy and safety of pharmacoinvasive (PI) strategy compared to primary percutaneous coronary intervention (PPCI) in the setting of a real-world ST-elevation myocardial infarction (STEMI) network where streptokinase (SK) is predominantly prescribed. Materials and Methods: The authors analyzed 325 STEMI patients who participated in The Siriraj STEMI network between July 2015 and October 2020. The primary efficacy endpoint was the incidence of cumulative major adverse cardiovascular and cerebrovascular events (MACCE) at one month, which were the composite of death, myocardial infarction, stroke, and non-coronary artery bypass graft (CABG)-related thrombolysis in myocardial infarction (TIMI) major or minor bleeding. The safety endpoint was non-CABG-related TIMI major or minor bleeding during the index hospitalization. Cox regression was performed for survival analysis. The authors applied propensity score matching to reduce the bias of the confounding variables. Results: Two hundred four patients received fibrinolytic therapy, 191 (93.6%) obtained SK, and 121 participants underwent PPCI. After propensity score matching analysis, the incidence of cumulative MACCE at one-month follow-up was not significantly different between the PI and the PPCI group (p=0.726) as well as the incidence of bleeding endpoint (p=0.446). In the subgroup analysis of the 191 patients who received SK (SK-PI), there was no statistical difference in the occurrence of cumulative MACCE compared to PPCI (p=0.136). Killip classification class III (hazard ratio [HR] 7.50, 95% confidence interval [CI] 3.25 to 17.31, p<0.001), and class IV (HR 9.78, 95% CI 4.31 to 22.21, p<0.001) were independent risk factors for developing MACCE. Conclusion: The streptokinase-based pharmacoinvasive strategy is non-statistically different in terms of efficacy and safety compared to PPCI. This evidence supports the utilization of the SK-PI approach in low- to middle-income countries where the availability of fibrin-specific fibrinolytic agents is often limited.